(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Residual stress can have a significant influence on the corrosion behaviour of low-carbon steel, which is a widely used material in various industries. Low-carbon steel is widely used in industrial applications, such as construction and automotive manufacturing, due to its low cost and good mechanical properties. The primary drawback of low-carbon steel is its high corrosion sensitivity, which can lead to catastrophic failures and substantial economic losses in certain circumstances. This study investigates the effect of residual stresses on the corrosion behaviour of low-carbon steel. According to the results of this study, it is evident that compressive residual stresses can enhance the corrosion resistance of low-carbon steel.